Performing shielding calculations for diagnostic radiology based on NCRP Report 147 Methodology - Mustafa Majali; Ali Al Remeithi (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2020)
Structural radiation shielding calculations for diagnostic X-ray facilities is most commonly performed using the recommendations of National Council on Radiation Protection and Measurements (NCRP) Report No. 49 which continues to be the primary guide for diagnostic x-ray structural shielding design for a while.  Many changes have occurred over the years that have caused the NCRP Report 49 calculation methodology to become essentially obsolete in that it did not address technology advances in Radiology. The methodology was remedied with the release of NCRP Report No. 147 by enabling shielding designers to, in part, specify effective barriers to diagnostic radiation environments. The NCRP Report 147 methodology for calculating radiation shielding requirements depend greatly on the shielding design goals (P) where a proposed design limit for controlled and uncontrolled areas is reduced to NCRP Report 49 levels. Further, the methodology most likely uses the concept of "dose constraint" in radiation installations as shielding design goals for the purpose of safety and protection optimization for occupational workers and the public. The previous NCRP Report 49 uses a very conservative approach in the assumption and methodology, which in return yielded with barriers much thicker than what is required in diagnostic facilities. In this context, Federal Authority for Nuclear Regulation (FANR), the nuclear and radiological regulator for the United Arab Emirates, recently published software which developed by authors for performing radiation shielding calculations based on an algebraic computation model and the given fitting factors provided by NCRP Report No. 147. The International Atomic Energy Agency (IAEA), has taken interest to independently validate the codes of the software; and praise the functionality of the tool. The software performs shielding calculations in an effective, easy, and reliable way while being a cost-effective and a timesaving tool.